Organizational factors and risk management practice of Malaysian contractors: the moderating role of coercive pressure - Manal Suliman, Omer Tagad (2023)
The construction sector is one of the significant sectors supporting the Malaysian economy. The nature of construction works has made it liable to risk, thereby making risk management an integral part of project management, particularly in developing countries. Experts from the academic and construction circles have been studying risk management's effectiveness concerning the encountered problems and the solutions. This study’s objectives are to evaluate the level of construction risk management practices among the large construction contractors (G7 contractors) operating in Peninsular Malaysia, to examine the effect of organizational structure and organizational internal factors on construction risk management practices, and the moderating role of coercive pressure. A proportionate stratified random sampling technique was deployed in selecting construction firms (registered with the Construction Industry Development Board Malaysia) for the survey. A total of 171 contractors from the eleven (11) states of Peninsular Malaysia partook in the study with a 48% valid response rate. A 5- point rating scale and a descriptive statistic were used to achieve the first research objective. SPSS ver.26 and structural equation modeling (SEM) in smart PLS software were employed in testing this study’s hypothesized paths. The level of risk management practices among Malaysian construction firms was found to be high. Drawing from organizational control and institutional theories, this study equally examined the role of coercive pressure on the correlation between organizational structure, organizational internal factors, and construction risk management practices. The findings showed that organizational structure and organizational internal factors had positive relationship with construction risk management practices. Likewise, coercive pressure positively moderated the relationship between centralization structure and construction risk management practices. The findings demonstrated that coercive pressure couldn't moderate the relationship between organizational internal factors and risk management practices among the construction industry operating in Malaysia. This study contributes to the growing body of knowledge within this domain by integrating construction risk management practices, organizational structure, organizational internal factors, and coercive pressure in single research focusing on the Malaysian construction industry. Consequently, this study might serve as a yardstick or benchmark towards risk.